EXTENT OF SOME HEAVY METALS CONTAMINATION IN SOIL OF FARMLANDS AROUND SOKOTO METROPOLIS - S. A. Zauro; M. U. Dabai; A. I. Tsafe; K. J. Umar; A. M. Lawal (European Scientific Journal, ESJ, 2013)
Soil samples were collected from six different farmlands along the major roads at the outskirt of Sokoto metropolis. The samples were digested and the filtrate subjected to quantitative analysis using Atomic Absorption spectroscopy (AAS). The results indicated the presence of all the metals under consideration apart from cadmium in FSI and FDU. The concentration of all the metals in all the samples area were below the standard set up by NYS DEC in soil with exception of Cr in FK. High levels ofCr in FK could be attributed to traffic Volume tanning processes taking place in the areas. The results also revealed that significant (p<0.05) difference exist between the samples in terms of heavy metals concentration.